Overview of the Neutrinos from Stored Muons Facility - nuSTORM. (19th July 2017) - Adey, D.; Appleby, R.B.; Bayes, R.; Bogacz, A.; Bross, A.D.; Lagrange, J.-B.; Liu, A.; Neuffer, D.; Pasternak, J.; Tygier, S.
Abstract: Neutrino beams produced from the decay of muons in a racetrack-like decay ring (the so called Neutrino Factory) provide a powerful way to study neutrino oscillation physics and, in addition, provide unique beams for neutrino interaction studies. The Neutrinos from STORed Muons (nuSTORM) facility uses a neutrino factory-like design. Due to the particular nature of nuSTORM, it can also provide an intense, very pure, muon neutrino beam from pion decay. This so-called "Neo-conventional" muon-neutrino beam from nuSTORM makes nuSTORM a hybrid neutrino factory. In this paper we describe the facility and give a detailed description of the neutrino beams that are available and the precision to which they can be characterized. We then show its potential for a neutrino interaction physics program and present sensitivity plots that indicate how well the facility can perform for short-baseline oscillation searches. Finally, we comment on the performance potential of a "Neo-conventional" muon neutrino beam optimized for long-baseline neutrino-oscillation physics.